Long-term outcomes of intravenous fibrinolysis in central retinal artery occlusion - Kozner, Pavel; Eichenmann, Libor; Ceska Burdova, Marie; Pavlikova, Marketa; Hlozanek, Martin; Dotrelova, Dagmar (Scientific reports, 2023)
Central retinal artery occlusion (CRAO) is an ophthalmologic emergency that can lead to irreversible loss of vision. Intravenous thrombolysis (IVT) has been used experimentally for its treatment. Our study aimed to evaluate the effect of emergency IVT on CRAO and its impact on visual acuity outcomes. We conducted a retrospective observational study of patients with CRAO. A total of 46 patients with CRAO were analysed; 16 patients received IVT treatment (IVT group) while 30 did not (no-IVT group). Seven patients from the IVT group received IVT early, within 4.5 hours (h) after the onset of symptoms (early-IVT), and 9 patients received it beyond this timeframe (late-IVT). The median time-to-hospital was 8.5 h: 3 h for the IVT group and 24 h for the no-IVT group. The median time-to-treatment was 5 h. The median outcome of visual acuity was 0.05 in the early-IVT, 0.025 in the late-IVT, and 0.01 in the no-IVT group. Among patients who received IVT early, 86% exhibited significant visual improvement. This improvement was four-fold greater compared to all other groups (p = 0.040), including the late-IVT (p = 0.011) and no-IVT groups (p = 0.023). No complications of the treatment were reported. Our study confirms that the administration of IVT treatment for CRAO within the 4.5-h time window is both safe and effective.
Keywords: fibrinolytická aktivita; trombolytická terapie; výsledek terapie; Thrombolytic Therapy; okluze retinální arterie; Treatment Outcome; fibrinolýza; lidé; Retinal Artery Occlusion; Fibrin Clot Lysis Time; Fibrinolysis; intravenózní podání; Administration, Intravenous; Humans